Drug-like molecules with anti-trypanothione synthetase activity identified by high throughput screening - Diego Benítez; Jaime Franco; Florencia Sardi; Alejandro Leyva; Rosario Durán; Gahee Choi; Gyongseon Yang; Taehee Kim; Namyoul Kim; Jinyeong Heo; Kideok Kim; Honggun Lee; et al. (Journal of Enzyme Inhibition and Medicinal Chemistry)
Trypanothione synthetase (TryS) catalyses the synthesis of N1,N8-bis(glutathionyl)spermidine (trypanothione), which is the main low molecular mass thiol supporting several redox functions in trypanosomatids. TryS attracts attention as molecular target for drug development against pathogens causing severe and fatal diseases in mammals. A drug discovery campaign aimed to identify and characterise new inhibitors of TryS with promising biological activity was conducted. A large compound library (n = 51,624), most of them bearing drug-like properties, was primarily screened against TryS from Trypanosoma brucei (TbTryS). With a true-hit rate of 0.056%, several of the TbTryS hits (IC50 from 1.2 to 36 µM) also targeted the homologue enzyme from Leishmania infantum and Trypanosoma cruzi (IC50 values from 2.6 to 40 µM). Calmidazolium chloride and Ebselen stand out for their multi-species anti-TryS activity at low µM concentrations (IC50 from 2.6 to 13.8 µM). The moieties carboxy piperidine amide and amide methyl thiazole phenyl were identified as novel TbTryS inhibitor scaffolds. Several of the TryS hits presented one-digit µM EC50 against T. cruzi and L. donovani amastigotes but proved cytotoxic against the human osteosarcoma and macrophage host cells (selectivity index ≤ 3). In contrast, seven hits showed a significantly higher selectivity against T. b. brucei (selectivity index from 11 to 182). Non-invasive redox assays confirmed that Ebselen, a multi-TryS inhibitor, induces an intracellular oxidative milieu in bloodstream T. b. brucei. Kinetic and mass spectrometry analysis revealed that Ebselen is a slow-binding inhibitor that modifies irreversible a highly conserved cysteine residue from the TryS’s synthetase domain. The most potent TbTryS inhibitor (a singleton containing an adamantine moiety) exerted a non-covalent, non-competitive (with any of the substrates) inhibition of the enzyme. These data feed the drug discovery pipeline for trypanosomatids with novel and valuable information on chemical entities with drug potential.